Insuficiencia renal crónica e hipertensión arterial en paciente femenino de 45 años. - Villacreses Carriel, Priscila Nohelia (2019)
The present work is based on a 45-year-old female patient, divorced Approximately 6 years ago by economist profession, has two daughters from the of Guayaquil, has been diagnosed for 4 years with chronic renal failure and since that time hemodialysis is being performed three times a week, the patient goes to the clinic to check her pressure and weight. The laboratory results show us a diagnosis of hyperkalemia and anemia and presents nausea and vomiting 2 days ago. It does not refer allergies. The physical examinations performed show a dehydrated skin, a dry weight of 58 kg/m2, height of 1.68 cm, blood pressure 135/90 mm/hg, arm circumference 20.1cm/mm, muscle circumference of the arm 20.1 mm, panicle of triceps 9.5 cm. The results of the anthropometric assessment reflect that the patient maintains her BMI at 20.5 kg/m2 where it is within the normal limits given. It manifests in the clinical aspects improvement in nutritional status, the respective caloric requirements are applied.